2007
DOI: 10.1007/s00276-007-0187-3
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical study of innervated transverse rectus abdominis musculocutaneous and deep inferior epigastric perforator flaps

Abstract: The present study investigated anterior cutaneous branches of the 10th, 11th and 12th intercostal nerves. Innervated transverse rectus abdominis musculocutaneous (TRAM) flap and deep inferior epigastric perforator (DIEP) flap are often used in breast reconstruction. To innervate these flaps effectively, the appropriate anterior cutaneous branches of intercostal nerves must be selected. Dissection of 40 sides of 20 cadavers (5 male, 15 female) was performed. Nerves were classified into four groups according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 10 publications
1
17
1
Order By: Relevance
“…Yap et al (2002) confirmed this, naming these large trunk communications, the ''intercostal plexus'' (Yap et al, 2002). Whilst other studies have also noted this extensive communication (Sakamoto et al, 1996;Mori et al, 2007), some have failed to observe communication between any or all of the segmental nerves at all (Monkhouse and Khalique, 1986;Duchateau et al, 1988).…”
Section: Clinical Applicationsmentioning
confidence: 62%
See 2 more Smart Citations
“…Yap et al (2002) confirmed this, naming these large trunk communications, the ''intercostal plexus'' (Yap et al, 2002). Whilst other studies have also noted this extensive communication (Sakamoto et al, 1996;Mori et al, 2007), some have failed to observe communication between any or all of the segmental nerves at all (Monkhouse and Khalique, 1986;Duchateau et al, 1988).…”
Section: Clinical Applicationsmentioning
confidence: 62%
“…Yap et al (2002) described such a plexus, by stating that ''nerves are closely related to the DIEA vascular axis'' (Yap et al, 2002) and other authors have also described communications at this level (Monkhouse and Khalique, 1986;Hammond et al, 1995;Tansatit et al, 2006). In contrast, some authors did not report communications between adjacent segmental nerves at this site (Duchateau et al, 1988;Mori et al, 2007). This longitudinal plexus was confirmed histologically as containing multiple nerves (see Fig.…”
Section: Clinical Applicationsmentioning
confidence: 68%
See 1 more Smart Citation
“…The mixed intercostals nerves deliver sensory branches joining with the perforating vessels of deep inferior epigastric vessels and running together to the skin. 3,4 If the sensory branches of the 11th intercostal nerves were chosen to be coapted with the dorsal penile nerves, the neopenis would recover more perfectly. Any of the sensory branches of the 10th, 11th, or 12th intercostal nerve could be chosen according to the selected perforators.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the use of innervated autologous flaps in breast reconstruction can provide protection from flap injury and trauma, recovery of erogenous sensation, and an overall higher patient satisfaction. [2][3][4][5][6][7] Despite these advantages, breast reinnervation is not commonly performed due to concern of extended operative time and variable clinical results. Furthermore, several studies have reported spontaneous reinnervation of flaps from adjacent skin.…”
mentioning
confidence: 99%